Model of motivational forces influencing academic achievement among secondary school students through the mediation of flow - Syed Mustafa, Sharifah Muzila (2015)
Motivation is a combined force that influences students to work hard and achieve academically. However, motivational force alone is not adequately strong to ensure students perform well in their academic tasks. There is a missing link between motivation and academic achievement which can be filled by flow, defined as an optimal state of engagement, concentration and enjoyment when doing a task. Students must get deeply engrossed,concentrated and focused on their learning tasks in order to perform better in school tasks and examinations. Therefore, this study proposed that when students have the motivation to perform well, they will get into flow when studying and subsequently achieve higher marks in examinations. The purpose of this study was to test a structural equation model of six motivational variables that influence academic achievement through the mediation of flow. The six motivational variables were future targets, achievement desire, learning goal, learning value, learning efficacy and learning regulation. A total of 395 Form Four students attending daily secondary schools in the state of Selangor responded to a set of questionnaire after their final year examination. Confirmatory factor analysis showed that the initial model of six motivational constructs had to be re-specified where five motivational constructs were combined into one major construct renamed as „intrinsic‟. The five variables were future targets, achievement desire, learning value, mastery goal and learning regulation. This resulted in a re-specified model with three motivational constructs: intrinsic, performance goal and learning efficacy. Evidently, analysis on the modified structural equation model showed that the three motivational constructs had no direct effect on academic achievement. Intrinsic and learning efficacy, but not performance goal, had direct effects on flow. Flow had a significantly positive effect on academic achievement. It was established that intrinsic and learning efficacy had indirect effects on academic achievement through the mediation of flow. It can be concluded that students with higher intrinsic and learning efficacy motivation were more likely to experience higher flow and thus perform better in their examination. The accepted model has highlighted the complex interactions of motivation and flow that contributed to students‟ achievement in school. The focus on flow theory has emphasized the importance of being in this state in order to improve concentration, engagement and therefore learning. It is recommended that students be exposed to the concept of flow and to appreciate the importance of achieving it when they perform a learning task. Teachers can also create training programs or workshops to educate students on ways to achieve a flow state as well as have high levels of motivation.